2016
DOI: 10.1080/07317115.2016.1203382
|View full text |Cite
|
Sign up to set email alerts
|

Financial Capacity and Financial Exploitation of Older Adults: Research Findings, Policy Recommendations and Clinical Implications

Abstract: Financial exploitation (FE) of older adults is a social issue that is beginning to receive the attention that it deserves in the media thanks to some high profile cases, but empirical research and clinical guidelines on the topic are just emerging. Our review describes the significance of the problem, proposes a theoretical model for conceptualizing FE, and summarizes related areas of research that may be useful to consider in the understanding of FE. We discuss structural issues that have limited intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The knowledge or awareness that one is having memory problems serves as a cue for a patient to adopt compensatory strategies such as making notes, using a planner or a memory app, or seeking assistance from others with certain tasks [5]. Conversely, individuals who are unaware of their cognitive deficits are vulnerable to making decisions that may endanger themselves and their caregivers, both physically (e.g., leaving the stove on, driving unsafely) and financially (e.g., falling victim to scams) [45, 72]. Indeed, one study found that individuals with mild AD who had reduced awareness of their memory abilities were less likely to implement compensatory strategies for managing their medications [18].…”
Section: Implications For Studying Self-awarenessmentioning
confidence: 99%
“…The knowledge or awareness that one is having memory problems serves as a cue for a patient to adopt compensatory strategies such as making notes, using a planner or a memory app, or seeking assistance from others with certain tasks [5]. Conversely, individuals who are unaware of their cognitive deficits are vulnerable to making decisions that may endanger themselves and their caregivers, both physically (e.g., leaving the stove on, driving unsafely) and financially (e.g., falling victim to scams) [45, 72]. Indeed, one study found that individuals with mild AD who had reduced awareness of their memory abilities were less likely to implement compensatory strategies for managing their medications [18].…”
Section: Implications For Studying Self-awarenessmentioning
confidence: 99%
“…At the same time that individuals with early-stage AD may by themselves be susceptible to poor financial outcomes, they are also more likely to be susceptible to financial exploitation and fraud by others (Stiegel, 2012;Wood & Lichtenberg, 2017). At the same time that individuals with early-stage AD may by themselves be susceptible to poor financial outcomes, they are also more likely to be susceptible to financial exploitation and fraud by others (Stiegel, 2012;Wood & Lichtenberg, 2017).…”
mentioning
confidence: 99%
“…Declining financial skills associated with early-stage AD may affect an individual's ability to sustain processes and behaviors that have guided their financial lives prior to cognitive impairment, such as those that ensure bills are paid on time, spending is kept in check, and investments are wise. At the same time that individuals with early-stage AD may by themselves be susceptible to poor financial outcomes, they are also more likely to be susceptible to financial exploitation and fraud by others (Stiegel, 2012;Wood & Lichtenberg, 2017). The National Center on Elder Abuse defines financial exploitation as the misappropriation of an older person's money or property (National Center on Elder Abuse, 2019), which can take forms such as theft, scams, unauthorized access to accounts, and improper use of guardianship (Wood & Lichtenberg, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We begin our special issue on capacity with a review of financial exploitation by Wood and Lichtenberg (2017). I suspect that most of our readers have been stunned and angered when they have encountered the sophisticated and devious approaches to defrauding an older family member or client.…”
mentioning
confidence: 99%